The Effect of Workplace Social Support (Supervisor and Co-Worker Support) on Job Performance With Work Engagement As A Mediator (A Study of LPSE UO Operators ff The Tni Headquarters) - Hermawan, P.Y. Deni; Atmoko, Andreo Wahyudi (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the direct influence between supervisor support and job performance on LPSE operators of UO Mabes TNI Work Unit, and to analyze the direct influence between co-worker support and job performance on LPSE operators of UO Mabes TNI Work Unit. This study also aims to analyze the direct influence between supervisor support and work engagement on LPSE operators of UO Mabes TNI Work Unit, and the direct influence between co-worker support and work engagement on LPSE operators of UO Mabes TNI Work Unit. In addition, this study aims to analyze the direct influence of work engagement on job performance on LPSE operators of UO Mabes TNI Work Unit. Another objective is to analyze the indirect influence between supervisor support and job performance mediated by work engagement on LPSE operators of UO Mabes TNI Work Unit, and to analyze the indirect influence between co-worker support and job performance mediated by work engagement on LPSE operators of UO Mabes TNI Work Unit. This study adopts a positivist paradigm that focuses on finding the truth through an empirical and measurable approach, with an ontological view of realism that believes that reality can be expressed with clear evidence and can be tested scientifically. The methodology used is mixed methods, which combines quantitative and qualitative approaches to obtain more comprehensive and valid data. This study adopts an explanatory research type to explain the causal relationship between the variables studied and test existing theories. Based on this study, it is concluded that the results of the research data analysis show several important findings. First, there is no direct influence between support from superiors (supervisor support) and job performance on LPSE operators in the UO Mabes TNI Work Unit environment. Likewise, there is no direct influence between co-worker support and job performance on the same LPSE operators. However, support from superiors is proven to have a direct influence on the work engagement of LPSE operators, as well as support from co-workers which has a direct effect on the level of work engagement. In addition, it was found that work engagement has a significant direct effect on the job performance of LPSE operators. Furthermore, the results of the study also showed an indirect effect between support from superiors on job performance mediated by work engagement. The same thing was also found in co-worker support, which has an indirect effect on job performance, with work engagement as the mediator.